Monitoring the depth of anaesthesia using the new modified entropy sensors during supratentorial craniotomy: Our experience - Sharma, Richa; Manninen, Pirjo; Venkatraghavan, Lashmikumar (Journal of Neuroanaesthesiology and Critical Care, 2015)
Background: Monitoring the depth of anaesthesia can be a challenge in patients undergoing supratentorial craniotomy because the conventional sensors for both bispectral index and entropy monitors lose their contact with a brain after scalp elevation. The new sensors for the entropy monitor are more flexible and can be placed in different locations. The purpose of this study was to determine the feasibility on the use of new GE entropy sensors in monitoring depth of anaesthesia in patients undergoing supratentorial craniotomy. Materials and Methods: We retrospectively reviewed the data from 20 consecutive patients undergoing supratentorial craniotomy who had the monitoring of the depth of anaesthesia using modified entropy sensors. Prior to the induction of anaesthesia, the new GE entropy sensor (P/N M1038681) was applied in a modified fashion. We measured the state entropy (SE) and response entropy (RE) at 12 perioperative time points. Entropy values were compared with the clinical indices of depth of anaesthesia. Results: Data from 20 consecutive patients (orbitozygomatic craniotomy [10] and bifrontal craniotomy [10]) were analysed. Monitoring was possible in all the patients. The changes in entropy values correlated with clinical indices of depth of anaesthesia. However, some patients showed variations in absolute values (RE and SE) during the intraoperative period without any changes in the level of anaesthetic depth. Conclusions: Monitoring the depth of anaesthesia is feasible with the use of new entropy sensors in patients undergoing supratentorial craniotomy. In contrast to standard sensors, the new sensors offer flexibility with the placement.
Keywords: Bispectral index; depth of anaesthesia; entropy; neurosurgery